Effects of pH and concentration of sodium citrate anticoagulant on platelet aggregation measured by light transmission aggregometry induced by adenosine diphosphate. (2nd January 2018) - Germanovich, Ksenia; Femia, Eti Alessandra; Cheng, Chun Yan; Dovlatova, Natalia; Cattaneo, Marco
Abstract: The 2013 ISTH-SSC guidelines for the standardization of light transmission aggregometry (LTA) were largely based on expert consensus, as studies directly comparing LTA methodologies were lacking. We experimentally tested the cogency of ISTH-SSC recommendations pertaining to use of anticoagulant, in particular whether: (1) buffered citrate (BC) is preferable to unbuffered citrate (C); (2) the two recommended concentrations of sodium citrate (109 and 129 mM) are equivalent in terms of platelet aggregation (PA). Blood from 16 healthy volunteers was collected into BC and C (109 and 129 mM). PA was measured by LTA in platelet-rich plasma (PRP) stimulated by adenosine diphosphate (ADP) (2 μM) immediately after PRP preparation and up to 4 hr after blood collection; pH and platelet counts in PRP were measured in parallel. pH in PRP increased with time up to about 8 for all anticoagulants, although it was lower in BC than in C at all times. In BC, PA was lower at 45 min, but equivalent at all other times. PA was higher and more stable in sodium citrate 109 mM than in 129 mM at all times. The extent of PA did not change for up to 2 hr after blood collection, and subsequently dramatically decreased. In contrast with ISTH-SSC recommendations, (1) BC does not show advantages compared to C; (2) 109 mM citrate is preferable to 129 mM, because it better supports PA; and (3) LTA studies should be completed within 2 hr of blood collection, instead of the recommended 4 hr.